A study of National Health Service management of chronic osteoarthritis and low back pain. Issue 2 (27th March 2014) - Hart, Oliver R.; Uden, Ruth M.; McMullan, James E.; Ritchie, Mark S.; Williams, Timothy D.; Smith, Blair H.
<x content-type="archive" xml:space="preserve">Abstract</x> Aim To describe treatment and referral patterns and National Health Service resource use in patients with chronic pain associated with low back pain or osteoarthritis, from a Primary Care perspective. Background Osteoarthritis and low back pain are the two commonest debilitating causes of chronic pain, with high health and social costs, and particularly important in primary care. Understanding current practice and resource use in their management will inform health service and educational requirements and the design and optimisation of future care. Method Multi-centre, retrospective, descriptive study of adults (⩾18 years) with chronic pain arising from low back pain or osteoarthritis, identified through primary care records. Five general practices in Scotland, England (two), Northern Ireland and Wales. All patients with a diagnosis of low back pain or osteoarthritis made on or before 01/09/2006 who had received three or more prescriptions for pain medication were identified and a sub-sample randomly selected then consented to an in-depth review of their medical records (n=264). Data on management of chronic pain were collected retrospectively from patients' records for three years from diagnosis ('newly diagnosed' patients) or for the most recent three years ('established' patients). Findings Patients received a wide variety of pain medications with no overall common prescribing pattern. GP visits represented the majority of the resource use and 'newly diagnosed' patients were significantly more likely to visit their GP for pain management than 'established' patients. Although 'newly diagnosed' patients had more referrals outside the GP practice, the number of visits to secondary care for pain management was similar for both groups. Conclusion This retrospective study confirmed the complexity of managing these causes of chronic pain and the associated high resource use. It provides an in-depth picture of prescribing and referral patterns and of resource use.